Bird diversity in different vegetation types in the Pacific coastal plain of Guatemala - Sofia Aguilar-Jocol; Michelle Bustamante-Castillo; Marco Tax (Neotropical Biology and Conservation)
Guatemala’s Pacific coastal plain, although largely dominated by agricultural land, still contains patches of diverse vegetation that could be vital for supporting bird diversity. Despite the country’s recognition for its rich avian biodiversity, updated data on species richness in this region are still lacking. Understanding the role of different vegetation types in maintaining bird diversity is essential for developing targeted conservation strategies that can both preserve and improve biodiversity in these fragmented landscapes. In this study, we compared species richness and the composition of bird communities across four distinct vegetation types along Guatemala’s Pacific coastal plain and analyzed species turnover and replacement to understand how these habitats contribute to maintaining overall bird diversity at the study site. The avian community consisted predominantly of species adapted to open habitats, with generalist bird species prevailing and only a limited representation of species typical of the understory in subtropical wet forests. Additionally, the observed species turnover value suggests a moderate level of species replacement among different vegetation types at the study site. The moderate nestedness, wherein species-poor communities are subsets of more diverse ones, further implies a decline in overall biodiversity. These findings suggest that the homogenization of the avian community indicates that our study focused on isolated areas that remain in this transformed environment. Our findings argue that protecting and restoring seminatural patches, even modestly sized patches, can be critical for safeguarding biodiversity in human-dominated landscapes and highlight the importance of landscape-level conservation, which enables connectivity between habitat patches to support species with different ecological requirements.